A Symptom-Triggered Benzodiazepine Protocol Utilizing SAS and CIWA-Ar Scoring for the Treatment of Alcohol Withdrawal Syndrome in the Critically Ill. (February 2017) - Sen, Soumitra; Grgurich, Philip; Tulolo, Amanda; Smith-Freedman, Andrew; Lei, Yuxiu; Gray, Anthony; Dargin, James
Background: There are limited data on the efficacy of symptom-triggered therapy for alcohol withdrawal syndrome (AWS) in the intensive care unit (ICU).Objective: To evaluate the safety and efficacy of a symptom-triggered benzodiazepine protocol utilizing Riker Sedation Agitation Scale (SAS) scoring for the treatment of AWS in the ICU.Methods: We performed a before-and-after study in a medical ICU. A protocol incorporating SAS scoring and symptom-triggered benzodiazepine dosing was implemented in place of a protocol that utilized the Clinical Institute Withdrawal Assessment for Alcohol (CIWA-Ar) scale and fixed benzodiazepine dosing.Results: We enrolled 167 patients (135 in the preintervention and 32 in the postintervention group). The median duration of AWS was shorter in the postintervention (5, interquartile range [IQR] = 4-8 days) than in the preintervention group (8, IQR = 5-12 days; P < 0.01). Need for mechanical ventilation (31% vs 57%, P = 0.01), median ICU length of stay (LOS; 4, IQR = 2-7, vs 7, IQR = 4-11 days, P = 0.02), and hospital LOS (9, IQR = 6-13, vs 13, IQR = 9-18 days; P = 0.01) were less in the postintervention group. There was a reduction in mean total benzodiazepine exposure (74 ± 159 vs 450 ± 701 mg lorazepam; P < 0.01) in the postintervention group.Conclusion: A symptom-triggered benzodiazepine protocol utilizing SAS in critically ill patients is associated with a reduction in the duration of AWS treatment, benzodiazepine exposure, need for mechanical ventilation, and ICU and hospital LOS compared with a CIWA-Ar–based protocol using fixed benzodiazepine dosing.